Comportamento verbal e linguagens da experiência religiosa: contribuições da análise do comportamento para a hermenêutica bíblica. - Melo, Jair Rodrigues (2019)
The present work deals with contributions that Radical Behaviorism can offer to biblical hermeneutics. It will be proposed a new approach to the texts of Scripture from the theoretical methodological contributions of Behavior Analysis, especially with the concepts of "rules of behavior" applied to the understanding of the demands of conduct present in the Bible and their relation to the acquisition of behavioral repertoires . The objective of this study is to study the applicability of analytic behavioral psychology to the understanding of the functional aspects of the languages of religious experience present in texts of the Bible, whose reference for analysis will be the text that deals with the "decalogue" in Deuteronomy 5,6 10 . For this, a bibliographical research will be done and, in the course of the same, it will prove the pertinence of this approach to interpret the biblical texts. In this sense, the main contributions were: the analysis of functional aspects of the messages of the biblical texts, as well as the main forms of understanding the production of the texts in view of the acquisition of behavioral repertoires.